2023
DOI: 10.3892/ol.2023.13684
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil‑to‑lymphocyte ratio before each chemotherapy line predicts clinical outcomes in patients with unresectable gastric cancer

Abstract: The neutrophil-to-lymphocyte ratio (NLR) is a well-known prognostic biomarker for patients with gastric cancer (GC). However, for patients with GC treated with palliative chemotherapy, the predictive values of NLR remain obscure. Therefore, the present study evaluated the clinical impact of NLR in patients with GC treated with a series of chemotherapies. The present study retrospectively evaluated 83 patients with unresectable GC who received a series of chemotherapies. NLR in the blood was calculated before e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In addition, among the findings of this study was the significant role played by preoperative NLR in determining outcomes after CRS-HIPEC. A previous study revealed its application in dichotomizing the patients into the high- and the low-risk groups before each chemotherapy line for GC and success in predicting post-treatment outcomes [ 24 ]. Another study constructed a prediction model constituting NLR and CA19-9 in GC patients [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, among the findings of this study was the significant role played by preoperative NLR in determining outcomes after CRS-HIPEC. A previous study revealed its application in dichotomizing the patients into the high- and the low-risk groups before each chemotherapy line for GC and success in predicting post-treatment outcomes [ 24 ]. Another study constructed a prediction model constituting NLR and CA19-9 in GC patients [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…NLR appears to be a prominent factor in survival analysis, and we believe that more aggressive and progressive disease characteristics are reflected in tumor microenvironments. As an indicative prognostic factor, high serum NLR levels represent multifaceted evaluations of cancer patients, consisting of oncologic burden, tumor invasiveness, upregulation of inflammatory cancer-associated cytokines, decline of host anti-cancer immunity, and systemic-inflammation-associated malnutritional status [ 23 , 24 , 26 ]. In short, preoperative serum NLR is known to be associated not only with tumor characteristics, but also with patient attributes, including nutritional, functional, and immunological aspects [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%